A new phenomenon?. (23rd January 2017) - Ganci, S
Abstract: This letter describes an interesting optical phenomenon engaging the reflected images of a new tube LED lamp (an array of high luminosity LEDs substituting the old fluorescent lamps) on any convex glossy black surface.